Livelihood Assets Petani Sawah Tadah Hujan Pada Era Pandemi Covid-19 Di Desa Kalampadu Kabupaten Ogan Ilir - yulasteriyani; Randi; Dian Sri Andriani; Muhammad Izzudin (geoedusains: Jurnal Pendidikan Geografi, 2023)
This research aims to analyze the livelihood assets of the COVID-19 pandemic among rainfed rice farmers in Kalampadu Village, Muara Kuang District, and Ogan Ilir Regency. This research will discuss research issues through Ellis' theory about farmers' livelihood assets. Researchers used descriptive research with a qualitative approach because the issue of rural livelihoods requires farmer subjectivity and in-depth data analysis. Data collection techniques used were participatory observation, in-depth interviews, and literature studies. Researchers used a case study research strategy to identify farmers' socio-cultural-economic-ecological and farmer household assets. The research results show that farmer households have five livelihood assets: 1) natural resource capital, (2) physical capital, (3) human capital, (4) financial capital, and (5) social capital. Massive changes in the livelihood assets of farmer households in Kalampadu Village began with the COVID-19 pandemic, which caused most farmers to change professions to online trading (Lazada and Shope).